HUBUNGAN KECEPATAN LARI 60 METER DENGAN HASIL LOMPAT JAUH SISWA PUTRA SDN 013 SUKAMAJU KECAMATAN SINGINGI HILIR - Kasrawati '; Drs. Ramadi., S.Pd., M.Kes AIFO '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The problem in this research is the result of long jump student still has not said to be good, it is suspected because of the running speed 60 meters. Then, this study aims to determine there is a corelation the running speed 60 meters with long jump results of male students class V SDN 013 Sukamaju Singingi Hilir District. The research sample of the entire population as many as 14 people male students Class V SDN 013 Sukamaju Singingi Hilir district. Data obtained from tests running 60 meters and long jump. This type of research is a correlational study to look at the corelational between two or more variables. In this study, the research data that has been collected and analyzed and then that becomes the variable X is running speed 60 meters and into a variable Y is the long jump results. From the calculation results can be seen that large correlation value of the escape velocity of 60 meters with the results of the long jump male student class V SDN 013 Sukamaju District of Singingi Hilir is 0.435 or r value calculated at 0.662 At the table of values (Product Moment) (5%) of = 0532, or 0.662> 0532 this means r count> r table. Criteria for hypothesis testing Ho accepted if t is smaller than ttabel, but the results of the calculations show that (t> t table) or 3:06> 1.782, thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) that "there has speed ran 60 meters with the results of the long jump male student class V SDN 013 Sukamaju Singingi Hilir District. "accepted.Keywords : Running Speed 60 meters, Long Jump